Cysteamine therapy: a treatment for cystinosis, not a cure - Cherqui, Stephanie (2012)
Cystinosis as a clinical entity is a progressive dysfunction of multiple organs caused by the accumulation of cystine in the tissues, leading, for example, to end-stage renal failure, diabetes, hypothyroidism, myopathy, and central nervous system deterioration. Brodin-Sartorius and colleagues present a long-term study on the impact of cysteamine therapy on these complications. The data show that cysteamine improves the outcome and complications of cystinosis but does not prevent them.